Automatic music genre classification - Ajoodha, Ritesh (My University, 2014)
No abstract provided.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science. 2014.
Keywords: Classification--Music.; Classification.